PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Retno Kusuma Dewi; Bambang Widagdo (Universitas muhammadiyah malang, 2012)
PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOODCORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAANRetno Kusuma DewiDinas Pendidikan Pemuda dan Olahraga Kab.KediriE-mail: retnokusuma@yahoo.comBambang WidagdoUniversitas Muhammadiyah MalangE-mail: bwidagdo@gmail.comABSTRACTThis study aims to describe and examine the effect of Corporate Social Responsibility and GoodCorporate Governance on Corporate Performance in the manufacturing companies listed on theStock Exchange in 2010.This study built on the belief that with the implementation of the practice ofcorporate social responsibility (CSR), it will give assurance to stakeholders that the company hasdone a good corporate governance (GCG), which is expected to improve company performance.Data collection using purposive sampling to manufacturing companies listed on the Indonesia StockExchange in 2010. A total of 98 manufacturing firms are used as samples.Analytical techniques usedin this study using descriptive statistical analysis and pathway analysisThe results of this study indicate that the manufacturing companies listed on the Stock Exchange in2010 has done a good CSR, through disclosing social responsibility in the annual report.While theimplementation of GCG and ROE in the manufacturing companies listed on the Stock Exchange in2010 was bad.Corporate Social Responsibility significant influence on Good Corporate Governance,Good Corporate Governance significantly influence the performance of the company, CorporateSocial Responsibility significantly influence the performance of the company through good corporategovernance as an intervening variableKeywords: corporate social responsibility, good corporate governance, corporate performance